Kajian Ikonologi Erwin Panofsky pada Ilustrasi Serat Selarasa (1804): Sebuah Metode Konservasi Seni: - Wulandari, Wiwik Sri (Jurnal SeniRupa Warna, 2026)
Serat Selarasa (1804) is one of the important manuscripts in the Javanese cultural tradition that contains noble values. This manuscript consists of 296 pages with 163 of them being colored illustrations in the style of Wayang Purwa and the rest being text in Javanese letters, written manually in Javanese. This manuscript is one of the collections of the Yogyakarta Palace Scriptorium. The impetus for this research is because the manuscript is threatened with extinction and there is a vacuum regarding the study of Serat Selarasa. The aim is to explain the aesthetics, history, culture, symbolic meaning, and philosophy behind the illustrations of Serat Selarasa through Erwin Panofsky's theory, which has advantages in visual theory. The results of this study show the complexity of Panofsky's aesthetic-historical iconology method applied to the illustrations of Serat Selarasa as an important foundation before art conservators conduct material analysis and conservation actions for cultural objects.